PENGGUNAAN APLIKASI QUIZIZZ SEBAGAI MEDIA UNTUK MELAKSANAKAN EVALUASI PEMBELAJARAN - M. Andra Aditiyawarman; Meini Sondang; Lilik Hanifah; Lusiana Dewi Kusumayati (Jurnal Penelitian)
To stop the spread of the Covid-19 virus, the learning system in Indonesia is also adapting by providing options for the implementation of online, offline, or blended learning processes. The use of online learning media is an alternative to the implementation of learning that reduces the risk of direct interaction between students. One of the online learning media that can be used during the learning process in general and the evaluation of learning in particular is the use of the quiziz application. This study aims to describe the quizizz media as an evaluation application for classroom learning. Quiziz is an educational game application that is narrative and flexible in nature that can be used as a means of delivering material as well as an interesting and fun learning evaluation medium. This research is a descriptive qualitative research that uses observation data collection methods and library research or library research, namely reading, studying, and reviewing books and writings related to the discussion. Based on the research, the results that can be achieved in the Quizizz application as a learning medium are: (1) The increased enthusiasm of students during the learning process increases because quiziz is one of the online learning media that contains games (interactive quizzes); (2) The increasing ability of students to understand the questions independently can be seen from the results of the pre-test, post-test, practice questions, and material strengthening; (3) Students participate actively during the learning process; (4) The use of the quiziz application can train students' time management accuracy in working on questions; (5) The use of the quiziz application can train students' calmness to work on questions or quizzes. Thus it can be concluded that the Quizizz application media is very effectively used in the learning evaluation process.